The last outlaws : the desperate final days of the Dalton Gang - Clavin, Tom, 1954- (St. Martin's Press, 2023)
"The Last Outlaws is the thrilling true story of the last of the great gang of outlaws and the most brazen heist in history. The Dalton Gang consisted of four brothers and their rotating cast of accomplices who saw themselves as descended from the legendary James Gang. They soon became legends themselves, beginning their career as common horse thieves, before graduating to robbing banks and trains. On October 5, 1892, the Dalton Gang attempted the most brazen heist of that era: robbing two banks in broad daylight in Coffeyville, Kansas, simultaneously. The gang was made up of Grat, Bob and Emmett Dalton; Bill Power and Dick Broadwell. As the gang crossed the plaza to enter the two banks, the Daltons were recognized by townspeople, who raised the alarm. Citizens armed themselves with weapons from nearby hardware stores and were ready for the gang when they tried to leave the banks. The ensuing gun battle was a firefight of epic proportions. When the smoke cleared eight men were dead including Grat and Bob Dalton, Bill Power and Dick Broadwell. For the first time ever, the full story of the Dalton Gang's life of crime, culminating in this violent heist, are chronicled in detail--the final act of the Wild West, its last bloody gasp." --